Interpolation, Projection and Hierarchical Bases in Discontinuous Galerkin Methods. Issue 3 (5th August 2015) - Angermann, Lutz; Henke, Christian
Abstract The paper presents results on piecewise polynomial approximations of tensor product type in Sobolev-Slobodecki spaces by various interpolation and projection techniques, on error estimates for quadrature rules and projection operators based on hierarchical bases, and on inverse inequalities.